Application of PCR in heartwater epidemiology - Peter, T.F.; O'Callaghan, C.J.; Perry, Brian D.; Medley, G.F.; Mahan, S. (1997)
Heartwater is a severe tick-borne, non-contagious disease of ruminant livestock caused by the rickettsia Cowdria ruminantium, which is endemic in much of sub-Saharan Africa and in the Caribbean. Transmission occurs via ticks of the Amblyomma genus, primarily A. variegatum and A. hebraeum. Intense research efforts are presently directed towards developing new vaccines for heartwater which will provide safe, effective and less expensive control options to acaricide treatment and the blood-based vaccine currently in use (Mahan et al., 1995; Martinez et al., 1993). Essential to the successful implementation of these vaccines is a thorough understanding of heartwater epidemiology, in particular disease transmission dynamics in host and vector populations. Past studies on heartwater epidemiology have been limited by the difficulty in detecting C. ruminantium infection or exposure. The few antigen detection tests described, brain biopsy, ELISA, and xenodiagnosis with blood or ticks, cannot reliably detect infection past the clinical stage of disease, and are too cumbersome and lengthy for large scale use in field and experimental epidemiologic studies. Similarly, heartwater serological tests currently available lack the sensitivity and specificity required to be useful epidemiologic tools. The recent Development of a polymerase chain reaction (PCR) C. ruminantium detection assay of high sensitivity and specificity has permitted more rigorous analysis of infection dynamics (Mahan et al., 1992; Peter et al., 1995). The PCR assay can be applied quickly and inexpensively to large numbers of samples. However, while PCR performs well on infected ticks, it is not yet sensitive enough for single test detection of chronically infected ruminants, due to the very low levels of circulating rickesttsemia in such animals. Nevertheless, analysis of tick infections has allowed reasonably detailed investigation of transmission dynamics through the quantification of key variables such as field tick infection rate and the relative importance of adult and nymphal tick transmission. In addition, the importance of hosts as sources of infection at different stages of infection can be studied indirectly by anlaysis of infections established in ticks that feed on them. These analyses can provide valuable estimates of parameters required for mathematical models of heartwater transmission dynamics that evaluate the impact of current and alternate disease control strategies (O'Callaghahan et al., 1997).